Analytical investigation of the mass spectrum of tetraquarks with a relativistic approach - A. Ghasempour; N. Tazimi; M. Monemzadeh (European Physical Journal C: Particles and Fields, 2025)
Abstract In this paper, we study four-body systems and consider them as diquark–antidiquark. We use the Bethe–Salpeter equation (Schrödinger equation with relativistic kinematics) to calculate the binding energies and the mass of heavy tetraquarks with hidden charm and bottom structures. To solve the Bethe–Salpeter equation, we use the Hellmann potential and the Ansatz method and calculate the mass of tetraquarks X(3.872),  Y(3.940),  $$Z_{cs}(3.985),$$ Z cs ( 3.985 ) , X(4.140),  $$Z_{b}(10.610),$$ Z b ( 10.610 ) , and $$Z_{b}(10.650).$$ Z b ( 10.650 ) . Our results are in good agreement with theoretical and experimental data.